Halal Food Logistics: The Challenges among Food & Beverages Small and Medium Sizes Manufacturers - Norlila Mahidin; Adam Mohd Saifudin (International Journal of Supply Chain Management, 2017)
This paper presents a part of a larger study in the perspective of halal food logistics (HFL) towards halal food beverages (FB) manufacturers in Malaysia. The rising of halal product demands of Muslim consumers, mainly FB has increased the potential for implementation of HFL services. However, the current condition suggesting that there is a low demand of HFL due to some challenges arose throughout the halal supply chain. These challenges are described from two perspectives; logistics service providers (LSPs) that offering HFL services and the halal product's manufacturers, mainly from small and medium enterprises (SMEs). Some of the challenges were identified such as the complex management of warehousing and terminals, the lack of trust and knowledge, perceived risk, and others that related to the halal matters.